Relationship of Age, Iodine Consumption and Body Mass Index with Hypertension Incidence in Menopausal Women in Temanggung Regency - Br Gultom, Ria Fazelita; Nainggolan, Wiwiek Elsada; Khoiriyah, Fitri; Hidayati, Yusmalia; Lubis, Dita Anggriani; Agustia, Dilma'aarij Riski (Jurnal Mamangan, 2023)
Menopause is a phase in which women do not experience menstruation. Often when women face menopause have feelings of anxiety and fear. This situation is due to a decrease in the hormone estrogen, progesterone and sex hormones which can cause physical symptoms that may be experienced when reaching menopause, such as a sudden feeling of heat that attacks parts of the body and is even prone to hypertension. This study aims to describe the factors associated with the incidence of hypertension in postmenopausal women in the Temanggung Regency Working Area. This research uses quantitative research with a cross sectional study design, which is to study the relationship between the dependent variable (hypertension) and the independent variable (Age, Iodine Consumption and Body Mass Index). The sampling technique used in this study is porposive sampling, namely the researcher categorizes the inclusion and exclusion criteria of the respondent sample into the study until the number of subjects in the study is fulfilled totaling 12 respondents. The results showed that the majority of respondents were aged 51-60 (83.3%), iodine consumption (%), respondents who had a body mass index indicated by more nutrition (%). Chi Square analysis test, obtained the value of age with hypertension p value = 0.039, the value of todium consumption with hypertension p value = 0.033, the value of body mass index with hypertension p value = 0.033. This shows that the p value < value is 0.05 so Ha is accepted which means there is a relationship between age, iodine consumption and body mass index with hypertension.